Professionalism in Foreign Language Teaching: An Everlasting Challenge - Rodríguez Chaves, José David (2018)
This qualitative, exploratory study is aimed at inquiring the issue of professionalism of university English language professors. Previous research indicates that professionalism in English Language Teaching (ELT) has been a concern for the academia; nonetheless, new demands in the ELT career require teachers to constantly upgrade their perfor mance in order to comply with higher education standards. Hence, traits, pedagogical practices, professional development, and challenges of these professionals are shown in this paper. Through a questionnaire, results revealed that participants felt satisfied with most of the newest teaching competencies. This study also identifies flaws in some teaching fields, which could be improved with professional development updates.